Re-Planning of Evacuated Israeli Settlements - Alqasem, Israa (My University, 2017)
Most Palestinian cities and villages suffer from Israeli occupation and its land control. In this search I looked for the evacuated settlements and exploited it for the Palestinian interest Mainly this research treat this issue in the evacuated settlements and the distribution of services in it in a way serving the surrounding villages and finally made a master plan as a final layout